2019
DOI: 10.1002/dys.1643
|View full text |Cite
|
Sign up to set email alerts
|

Is part‐time special education beneficial for children at risk for reading difficulties? An example from Estonia

Abstract: This longitudinal quasi‐experimental study examined the general efficiency of part‐time special education for students at risk for reading difficulties in Estonian primary schools. Participants were selected from 464 students whose pre‐reading and reading skills were assessed for the study at the beginning of school. Eighty‐four of these children received part‐time special education support throughout the first grade (treatment group). Statistical matching was used to find a control group similar to the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 53 publications
1
8
0
1
Order By: Relevance
“…It has also been indicated that although some students do not show any difficulties in their early reading skills, they might turn up during their later school years (Kent et al, 2018;Torppa et al, 2015;Wanzek et al, 2010). Thus, we suggest that SEN teacher's role in supporting students' literacy learning is worth further investigation (see also Soodla et al, 2019). Areas to explore are how students' skills should be assessed to gain higher sensitivity and specificity, kinds of assessment and support practices SEN teachers use with students who have RD, and what the most effective practices are and why.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It has also been indicated that although some students do not show any difficulties in their early reading skills, they might turn up during their later school years (Kent et al, 2018;Torppa et al, 2015;Wanzek et al, 2010). Thus, we suggest that SEN teacher's role in supporting students' literacy learning is worth further investigation (see also Soodla et al, 2019). Areas to explore are how students' skills should be assessed to gain higher sensitivity and specificity, kinds of assessment and support practices SEN teachers use with students who have RD, and what the most effective practices are and why.…”
Section: Discussionmentioning
confidence: 67%
“…This study underlines that teachers need reliable assessment tools throughout primary grades to monitor students' reading progress systematically and continuously. For instance, as our study also shows, support decisions based mainly on teachers' own perceptions and observations of students' performances can lead to inaccurate assessments (see also Soodla et al, 2019). One solution for better judgment accuracy could be a structured assessment tool designed for special education purposes enabling teachers to rank-order students' reading performance and compare the rankings with the reading test scores.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…One possible reason for support specialists' more inaccurate judgements may be that, traditionally, support specialists work with students with learning difficulties in a separate room-mostly twice a week (Soodla et al, 2020); thus, they may not have an overview of the overall level of the class. As the general level of the class may influence the teacher's assessments (Kikas et al, 2018), it can be assumed that the same phenomenon could take place within a group of students attending special education classes.…”
Section: Teachers' and Support Specialists' Judgements About Sen Stud...mentioning
confidence: 99%
“…Whether a student needs general support is an in‐school pedagogical decision and does not require a formal diagnosis of learning disabilities. General support is usually arranged as a pull‐out service, and the frequency of support lessons depends on the individual needs, but students typically attend such sessions twice a week (Soodla, Tammik, & Kikas, 2020 ). In addition to special educators, speech therapists and remedial teachers work in Estonian schools and support students with reading and writing difficulties (Padrik & Kikas, 2007 ).…”
Section: Introductionmentioning
confidence: 99%